The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0100-879x2012007500007
|View full text |Cite
|
Sign up to set email alerts
|

The miR-17-92 cluster regulates FOG-2 expression and inhibits proliferation of mouse embryonic cardiomyocytes

Abstract: MicroRNAs (miRNAs) have gradually been recognized as regulators of embryonic development; however, relatively few miRNAs have been identified that regulate cardiac development. A series of recent papers have established an essential role for the miRNA-17-92 (miR-17-92) cluster of miRNAs in the development of the heart. Previous research has shown that the Friend of Gata-2 (FOG-2) is critical for cardiac development. To investigate the possibility that the miR-17-92 cluster regulates FOG-2 expression and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Forty‐eight hours after being transfected with plasmid or miRNA mimic, mK3 cells were briefly rinsed with PBS and lysed with 200 µl of radioimmunoprecipitation assay cell lysis buffer per well of a six‐well plate. Western blotting was performed as previously described . The lysate was resolved in 12% sodium dodecyl sulphate PAGE gel, and protein bands were transferred to the polyvinylidene difluoride membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty‐eight hours after being transfected with plasmid or miRNA mimic, mK3 cells were briefly rinsed with PBS and lysed with 200 µl of radioimmunoprecipitation assay cell lysis buffer per well of a six‐well plate. Western blotting was performed as previously described . The lysate was resolved in 12% sodium dodecyl sulphate PAGE gel, and protein bands were transferred to the polyvinylidene difluoride membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described. 15 The lysate was resolved in 12% sodium dodecyl sulphate PAGE gel, and protein bands were transferred to the polyvinylidene difluoride membrane. The membrane was hatched with primary antibody (rabbit anti-Six2, 1:600 dilution, Proteintech, USA, and mouse anti-β-tubulin, 1:3000 dilution, TransGen, China) at 4°overnight.…”
Section: Western Blottingmentioning
confidence: 99%
“…Another study based on embryonic cardiomyocytes reported that overexpression of miR-17-92 would reduce the cell proliferation through posttranscriptional repression of Friend of Gata-2 (FOG-2, a nuclear corepressor protein), which is a critical factor for cardiac development. Moreover, FOG-2 could partially rescue the abnormal proliferation induced by miR-17-92 [12]. In addition, miR-17-92 cluster member miR-19 promoted cardiomyocyte proliferation through direct downregulation of PTEN in vitro [21].…”
Section: The Role Of Mir-17-92 Cluster In Cardiovascular Diseasesmentioning
confidence: 99%
“…Among all miRNA clusters, miR-17-92, which was called oncomir-1 at first, is a highly conserved cluster that is essential in adipocyte differentiation [8], lung development [9], angiogenesis [10], tumorigenesis [11], and especially heart development [12, 13]. miR-17-92 cluster has been confirmed to be involved in normal cardiac development and its change took part in the genesis of many cardiovascular diseases, including heart failure [14], cardiomyopathy, arrhythmias, and cardiac hypertrophy [15], while its mechanisms of action in these contexts are not fully understood (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA clusters perform important functions by regulating various cellular processes. For example, the most frequently studied miR-17-92 cluster is involved in the development of the heart, lungs, and immune system and in the formation of tumors [13][15]. Clustered miRNAs are usually derived from a common primary transcript and coexpressed [16].…”
Section: Introductionmentioning
confidence: 99%